Lymphocyte Recovery After Breast Cancer Treatment and Mindfulness-Based Stress Reduction (MBSR) Therapy. (January 2013) - Lengacher, Cecile A.; Kip, Kevin E.; Post-White, Janice; Fitzgerald, Shirley; Newton, Cathy; Barta, Michelle; Jacobsen, Paul B.; Shelton, Melissa M.; Moscoso, Manolete; Johnson-Mallard, Versie; Harris, Eleanor; Loftus, Loretta; et al.
Objectives: This randomized controlled trial was conducted to examine immune recovery following breast cancer (BC) therapy and evaluate the effect of mindfulness-based stress reduction therapy (MBSR) on immune recovery with emphasis on lymphocyte subsets, T cell activation, and production of T-helper 1 (Th1; interferon [IFN]-γ) and T-helper 2 (Th2; interleukin-4 [IL-4]) cytokines. Method: Participants who completed the study consisted of 82 patients diagnosed with Stage 0–III BC, who received lumpectomy and adjuvant radiation ± chemotherapy. Patients were randomized into an MBSR(BC) intervention program or a control (usual care) group. Immune cell measures were assessed at baseline and within 2 weeks after the 6-week intervention. The numbers and percentages of lymphocyte subsets, activated T cells, and Th1 and Th2 cells in peripheral blood samples were determined by immunostaining and flow cytometry. Results: Immune subset recovery after cancer treatment showed positive associations with time since treatment completion. The B and natural killer (NK) cells were more susceptible than T cells in being suppressed by cancer treatment. Women who received MBSR(BC) had T cells more readily activated by the mitogen phytohemagglutinin (PHA) and an increase in the Th1/Th2 ratio. Activation was also higher for the MBSR(BC) group if <12 weeks from the end of treatment and women in MBSR(BC) <12 weeks had higher T cell count for CD4 + . Conclusion: MBSR(BC) promotes a more rapid recovery of functional T cells capable of being activated by a mitogen with the Th1 phenotype, whereas substantial recovery of B and NK cells after completion of cancer treatment appears to occur independent of stress-reducing interventions.